Effects of depressive symptomatology on cancer‐related symptoms during oral oncolytic treatment. Issue 1 (23rd October 2018) - Decker, Veronica; Sikorskii, Alla; Given, Charles W.; Given, Barbara A.; Vachon, Eric; Krauss, John C.
Abstract: Objective: This manuscript assesses association between depressive symptoms and symptoms from cancer and its treatment during the first 12 weeks of a new oral oncolytic treatment. Methods: This secondary analysis used data from a recently completed trial of an intervention to improve adherence to oral oncolytic treatment and manage symptoms. Following the initiation of the new oral oncolytic medication, 272 patients were interviewed at intake and weeks 4, 8, and 12 to assess depressive symptoms, and symptoms from cancer and its treatment. Depressive symptoms were measured using the Center for Epidemiologic Studies‐Depression (CES‐D20). The summed index of 18 cancer‐related and treatment‐related symptoms as well as the number of symptoms above threshold at intake, weeks 4, 8, and 12 were related to intake and time‐varying CES‐D20 using linear mixed effects models. Results: Depressive symptomatology was a significant predictor of cancer‐related and treatment‐related symptoms at all‐time points, but the strength of this relationship was greatest at the time of oral oncolytic agent initiation and at week 4. The strength of this relationship was the same for both summed symptom severity index and the number of symptoms above threshold, and using either intake or time‐varying CES‐D20. Conclusion: Introducing strategies to treat and manage symptoms of depression along with other symptoms might have added benefits among patients who start a new oral oncolytic treatment and report modest to higher levels of depressive symptoms. Assessments for the impact of strategies to lower depressive symptoms can be taken within the first 4 weeks.